Mechanisms of texture formation in thin-film systems Ni₁-xWx | TiN - Sungurov, M.S.; Sukhareva, T.V.; Finkel, V.A. (Functional Materials, 2018)
he article is devoted to study of the problem of establishing the nature and mechanisms of processes of texture formation in both components of a thin layer system Ni - 9.5 at. % W /TiN. Comparative analysis of the structure and properties of two-layer compositions based on tapes made of ferromagnetic Ni - 5 at. % W alloy and paramagnetic Ni - 9.5 at. % W alloy with TiN coating was carried out using X-ray diffraction analysis. It was established that the mechanism and kinetics of the texture formation processes are conduced by peculiarities of the redistribution of the stress state in both subsystems of the two-component substrate-coating system. Within the framework of the present work, the strategy for obtaining the textured substrates based on Ni - 9.5 at. % W alloy is developed, which makes it possible to create effective architecture of the high-temperature superconductors of the second generation (2G HTS) with the high current-carrying capacity.